Building Motivation for Research in Elementary School Students - Manat K. Zhailauova, Akbilek P. Mynbayeva,Nazgul T. Sartayev, Serik M. Kenesbayev, (Opción, 2019)
The article provides a theoretical framework for the problem of the development of research skills and motivation for research among elementary school students. Using such methods as analysis, synthesis, generalization, survey, diagnostics and practical tasks, comparative data were collected that show the level of elementary students’ motivation for research based on information technologies. As a result, the level of elementary students’ motivation for research based on information technologies increased. In conclusion, engaging children in research using information technologies stimulates the development of creative abilities and initiative at each level of learning.